2018
DOI: 10.1111/anu.12873
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of de-oiled rice bran inclusion level in the diet ofLabeo rohita: Effect on growth performance, nutrient utilization, insulin-like growth factors I and II gene expression

Abstract: A 60‐day feeding trial was conducted to optimize the inclusion level of de‐oiled rice bran (DORB) in the diet of Labeo rohita fingerlings. Six iso‐nitrogenous (260g/kg), iso‐lipidic (70g/kg) and iso‐energetic (15 MJ/Kg) diets were prepared with different inclusion level of DORB viz., T33, T38, T43, T48, T53 and T58. One hundred and eighty fingerlings (9.8 ± 0.5 g) were randomly distributed in seven experimental groups in triplicates following a completely randomized design. The weight gain %, specific growth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…A number of animal organs (the gut, liver, or kidney) synthesize IGF-I. But in fish, liver IGF-I is thought to be one of the most important growth mediators [ 91 , 92 ]. The nutritional condition of numerous fish species has a significant impact on hepatic IGF-1 levels [ 91 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of animal organs (the gut, liver, or kidney) synthesize IGF-I. But in fish, liver IGF-I is thought to be one of the most important growth mediators [ 91 , 92 ]. The nutritional condition of numerous fish species has a significant impact on hepatic IGF-1 levels [ 91 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…But in fish, liver IGF-I is thought to be one of the most important growth mediators [ 91 , 92 ]. The nutritional condition of numerous fish species has a significant impact on hepatic IGF-1 levels [ 91 , 93 ]. In current research, hepatic IGF-I expression was directly correlated with the optimum P/E ratio; however, as the P/E ratio increases or decreases further, the expression level of IGF-I diminishes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As DORB is widely distributed, easily available and cheapest, it is most commonly incorporated in fish farm‐made feed along with different oilcakes (Meshram et al, 2018; Ranjan et al, 2017, 2018, 2019). However, recent studies indicated that 33–40% inclusion of DORB in the carp diet does not affect the growth in rohu fingerlings (Kumar et al, 2018, 2018, 2019). Moreover, the growing competitions with livestock feed and human food sector would lower the availability of DORB in near future to aquafeed sector (FAO, 2017).…”
Section: Introductionmentioning
confidence: 99%